Turtles all the way down eaudiobook - Green, John (Listening Library, 2017)
FEATURED ON 60 MINUTES and FRESH AIR “So surprising and moving and true that I became completely unstrung.” –  The New York Times Named a best book of the year by:  The   New York Times,  NPR,  TIME ,  Wall Street Journal ,  Boston Globe ,  Entertainment Weekly ,  Southern Living ,  Publishers Weekly ,  BookPage ,   A.V. Club, Bustle, BuzzFeed, Vulture, and many more! JOHN GREEN , the acclaimed author of  Looking for Alaska  and  The Fault in Our Stars , returns with a story of shattering, unflinching clarity in this brilliant novel of love, resilience, and the power of lifelong friendship. Aza Holmes never intended to pursue   the disappearance of fugitive billionaire Russell Pickett, but there’s a hundred-thousand-dollar reward at stake and her Best and Most Fearless Friend, Daisy, is eager to investigate. So together, they navigate the short distance and broad divides that separate them from Pickett’s son Davis.  Aza is trying. She is trying to be a good daughter, a good friend, a good student, and maybe even a good detective, while also living within the ever-tightening spiral of her own thoughts.